A molecular investigation of the novel gene underlying autosomal dominant retinitis pigmentosa in a South African family - Bardien-Kruger, Soraya (Division of Human Genetics, 2018)
The inherited retinal degenerative disorders are a common cause of severe visual handicap in the W estem world. Retinitis pigmentosa (RP) is a group of retinopathies in which a primary feature is a progressive loss of photoreceptor and retinal pigment epithelium function. Over the last decade, investigations into the patho-physiology of RP have identified numerous disease-causing genes and loci (for a current listing refer to the web site http://www.sph.uth.tmc.edu/Retnet/). A study of a South African family with an autosomal dominant form of RP (adRP) forms the basis of this dissertation. In this family, comprising 44 individuals, the first manifestation of visual disturbance is usually evident between 20 and 30 years of age. Subsequently, another South African adRP family, consisting of 25 members, was also incorporated into this investigation. Genetic linkage analysis facilitated the mapping of the disease phenotype in the two South African adRP families to a 10 cM interval on chromosome 17q22. This novel locus, designated RP17, is the eighth identified for adRP. Haplotype construction in the two kindreds, in conjunction with multipoint analyses subsequently fine mapped RP17 to a 1 cM region between microsatellite markers D17S1604 and D17S948. Although the two families are from ethnically diverse population groups, they share the same disease-associated haplotype spanning 12 cM, which suggests that the disorder may be caused by the same pathogenic mutation in the same gene. The positional cloning approach was utilised in an endeavour to identify the RP17 gene and an attempt was made to construct a physical map of the 1 cM critical region. A contig consisting of seven yeast artificial chromosome (YAC) clones was assembled using sequence-tagged-site (STS) content mapping. In order to close a gap in the YAC contig, a bacterial artificial chromosome (BAC) library was screened and the vectorette PCR technique was used to verify overlapping sequences. This contig should provide a useful tool for the purpose of isolating genes or transcription units within the RP17 critical interval. In this regard, purified YAC DNA was isolated using pulsed-field gel electrophoresis and the cDNA selection technique was employed to generate a transcription map. This approach was applied to YAC 75Ic12 using a foetal brain cDNA library, and two rounds of selection were performed to create a sub-library for enriched cDNAs derived from this clone. Screening for the presence of contaminating sequences in the 480 transformants revealed that (i) approximately 7% of the selected clones contain COT-1 DNA and (ii) none of the clones were contaminated with yeast AB1380 DNA. Ten randomly chosen clones were sequenced and subjected to BLASTN analysis, which revealed the presence of a 23 bp contaminant, known genes as well as novel transcripts. In order to optimise efforts to isolate the adRP gene, four positional candidates residing on 17q were screened for evidence implicating them in the adRP phenotype in the two 17q22-linked families. The genes investigated were: PDEG (gamma subunit of rod phosphodiesterase), TIMP2 (tissue inhibitor of metalloproteinases-2), PKCA (protein kinase C alpha) and retinal fascin. These candidates were chosen on the basis of (i) mapping to 17q, (ii) expression in the retina and/or (iii) potential involvement in the rod phototransduction pathway. Recombination events between the adRP locus and a single strand conformation polymorphism (SSCP) in PDEG, and a restriction fragment length polymorphism (RFLP) in TIMP2 provided evidence for the exclusion of these candidate genes. A novel SSCP detected in the promoter region of retinal fascin was genotyped in the two adRP families and showed a lack of co-segregation with the disease locus. Furthermore, direct DNA sequencing of the coding regions as well as the promoter region of retinal fascin in RP affected family members did not reveal any pathogenic mutations. In addition, data is provided which suggests that PKCA does not reside on any of the YACs and BACs encompassing the RP17 critical interval. This gene is therefore unlikely to be responsible for the adRP phenotype in the two RP17-linked families. Ultimately, the work reported in this thesis may contribute to the body of knowledge on inherited retinal degenerative disorders. Moreover, this investigation should provide the basis for further study of the aetiology of RP in all families linked to the RP17 locus on chromosome 17q22. The immediate application of these molecular findings is the potential for pre-symptomatic testing of at-risk members from the two adRP kindreds.